Our Blind Spots in the Fight Against Health Systems Corruption; Comment on "We Need to Talk About Corruption in Health Systems" - Reinhard Huss (Kerman University of Medical Sciences, 2020)
The health sector often appears prominent in surveys of perceived corruption, because citizens experience the symptoms of systemic corruption most distressingly during their interaction with frontline health workers. However, the underlying drivers of systemic corruption in society may be located in other social systems with the health system demonstrating the symptoms but not the path how to exit the situation. We need to understand the mechanisms of systemic corruption including the role of corrupt national and international leaders, the role of transnational corporations and international financial flows. We require a corruption definition which goes beyond an exclusive focus on the corrupt individual and considers social systems and organisations facilitating corruption. Finally there is an urgent need to address the serious lack of funding and research in the area of systemic corruption, because it undermines the achievement of the Sustainable Development Goals (SDGs) in many low income countries with the most deprived populations.